Participation of Religious Leaders in Helping the Success of the Government's COVID-19 Vaccination Program - Simon Simon; Alfons Renaldo Tampenawas; Joko Santoso; Astrid Maryam Yvonny Nainupu; Semuel Ruddy Angkouw; Alvonce Poluan (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2021)
Participation of Religious Leaders in Helping the Success of the Government's COVID-19 Vaccination Program. The basic idea of this paper departs from observations in the virtual and real world, where certain people or groups are found who disagree with the need to be vaccinated. If the country's people reject the mandatory mass vaccination, which the government is discussing, it will take a long time to restore normal activities. This paper uses a descriptive qualitative method with a literature study approach. The description in this paper found some people's rejection of vaccines because their views or perceptions about COVID-19 influenced it. The government's hope to immediately carry out mass vaccinations for all Indonesian people must be balanced with maximum efforts to make it happen. This substantial effort can be made by providing massive education in the media, conducting public campaigns, and providing guarantees to vaccine recipients. On the other hand, the success of this vaccination program does not only depend on the government; all elements of society are expected to contribute in this regard, especially religious leaders. The manifestation of the involvement of religious leaders is by educating the congregation through the pulpit about vaccines. In addition, religious leaders must also set an example by participating in vaccinations and actively countering hoax news. The dominance of factual information about vaccines dominates mass lines on social media. ABSTRAKKeikutsertaan Pemuka Agama Dalam Membantu Mensukseskan Program Vaksinasi COVID-19 Pemerintah. Ide dasar tulisan ini berangkat dari pengamatan di dunia maya dan nyata, yang mana ditemukan orang-orang atau kelompok tertentu yang tidak menyetujui keharusan untuk divaksin. Apabila masyarakat tanah air kecenderungan menolak wajib vaksinasi masal yang diwacanakan oleh pemerintah, tentu akan lama memulihkan aktivitas normal kembali. Tulisan ini menggunakan metode kualitatif deskriptif dengan pendekatan studi literatur. Uraian pada tulisan ini ditemukan, penolakan sebagian orang terhadap vaksin karena dipengaruhi oleh  pandangan atau persepsi mereka mengenai COVID-19. Harapan pemerintah untuk segera melakukan vaksinasi masal ke seluruh masyarakat tanah air, harus diimbangi upaya yang maksimal dalam mewujudkannya. Upaya konkret itu dapat dilakukan dengan pemberian edukasi secara masif di media, melakukan kampanye publik dan adanya jaminan kepada penerima vaksin. Disisi lain suksesnya program vaksinasi ini tidak hanya bergantung kepada pemerintah, semua elemen masyarakat diharapkan kontribusinya dalam hal ini terutama para pemuka agama. Wujud dari keterlibatan pemuka agama adalah dengan mengedukasi jemaat melalui mimbar tentang vaksin. Selain itu, pemuka agama juga harus memberi contoh dengan ikut divaksin, serta aktif mengcounter berita hoax agar dominasi berita faktual tentang vaksin menguasai lini massa  di media sosial.